2014
DOI: 10.1378/chest.13-2306
|View full text |Cite
|
Sign up to set email alerts
|

B-Mode Ultrasound Assessment of Diaphragm Structure and Function in Patients With COPD

Abstract: BACKGROUND: Electromyographic evaluation of diaphragmatic neuromuscular disease in patients with COPD is technically diffi cult and potentially high risk. Defi ning standard values for diaphragm thickness and thickening ratio using B-mode ultrasound may provide a simpler, safer means of evaluating these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 27 publications
4
92
0
7
Order By: Relevance
“…The authors showed that diaphragm thickness measured by ultrasound was significantly correlated with that directly measured by a ruler. 92 Since then, several studies have been performed to establish reference values of diaphragm thickness in supine healthy subjects, showing for the right hemidiaphragm mean values of 0.32 cm 93 or 0.33 cm, 94 independent of sex, age, or body constitution. More recently, Baldwin et al 95 described a mean diaphragm thickness value of 1.73 mm (range 1.11-2.98) when measured at end expiration in healthy volunteers.…”
Section: B-modementioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that diaphragm thickness measured by ultrasound was significantly correlated with that directly measured by a ruler. 92 Since then, several studies have been performed to establish reference values of diaphragm thickness in supine healthy subjects, showing for the right hemidiaphragm mean values of 0.32 cm 93 or 0.33 cm, 94 independent of sex, age, or body constitution. More recently, Baldwin et al 95 described a mean diaphragm thickness value of 1.73 mm (range 1.11-2.98) when measured at end expiration in healthy volunteers.…”
Section: B-modementioning
confidence: 99%
“…Other authors reported how left hemidiaphragm measurements could not be consistently obtained, whereas right hemidiaphragm thickness measurements are highly reproducible, particularly after marking the location of the probe. 87 Some authors evaluated the variation of thickness at different lung volumes from RV to TLC in normal subjects, [90][91][92][93] suggesting the use of this maximal contractile capacity of the diaphragm. Another study measured diaphragm thickness in subjects with diaphragm paralysis to monitor recovery of the muscle over time.…”
Section: B-modementioning
confidence: 99%
“…Baria et al had a similar study to ours with B-mode US where diaphragmatic thickness and thickening ratio were measured in COPD patients with coexisting neuromuscular respiratory weakness. No significant difference was found between COPD patients and healthy groups in terms of diaphragm thickness with the exception of a subgroup with severe air trapping so Baria et al concluded that normal values could be applied to COPD patients as reference values [4].…”
Section: Discussionmentioning
confidence: 99%
“…Studies dealing with inspiratory muscle weakness in COPD patients focus mostly on diaphragm since it is the principal generator of tidal volume [3]. US findings of diaphragm muscle in COPD patients is not concluded yet because of the varying results [3][4][5][6][7].These studies address the structure and the motion of the diaphragm [4]. The impairment of diaphragm is suggested to be an important factor which is associated with alterations in the principal pulmonary function parameters such as FEV1 [8].…”
Section: Introductionmentioning
confidence: 99%
“…A thickness <0.2 cm measured at the end of expiration has been proposed as a cut-off to define diaphragm atrophy. These values apply when assessing the neuromuscular status of the diaphragm in patients with chronic obstructive pulmonary disease (COPD) (29). Excursion is best measured in the M-mode, and the normal range of motion from the resting expiratory position to full inspiration is 1.9-9 cm in adults with higher values reported in deep breathing or sniffing.…”
Section: Diaphragmatic Pathologymentioning
confidence: 99%